Kadın eğitimi açısından Mehmed Zihni Efendi - Kılıçaslan, Lütfiye (My University, 2019)
Osmanlı Devleti’nin son dönemlerinde Tanzimat Fermanı’yla (1839) başlayan ve II. Meşrutiyet’in (1908) ilanı ile devam eden yenilik anlayışı eğitime de yansımıştır. Kadınların eğitim alacağı kurumlar ve müfredatlar yenilenmiştir. Son dönem Osmanlı âlimlerinden olan Mehmed Zihni Efendi (1846 - 1913) bu döneme şahitlik etmiş ve ilmi kişiliğiyle ön plana çıkmıştır.Bu çalışmada Zihni Efendi’nin kadın eğitimine ve öğretimine katkısı, ilkokul üçüncü ve dördüncü sınıfların kız şubelerinde okutulmak üzere kaleme aldığı Kızlar Hocası ve Hanımlar İlmihali adlı ders kitapları çerçevesinde incelenmiştir.

In the last period of the Ottoman Empire, the conception of innovation that began with the Imperial Edict of Gulhane (1839) and continued with the second constitutionalist period (1908), was also reflected in education. Institutions and curricula which women will receive education have been renewed. Mehmed Zihni Efendi (1846 - 1913), one of the scholars of the last period of Ottoman Empire, witnessed this period of innovation and came to the forefront with his scientific personality.In this study, the contributions of Zihni Efendi to the education and training of women has been examined within the framework of the textbooks named Kızlar Hocası ve Hanımlar İlmihâli, which were written to be taught at the girls' branches of the third and fourth grades of primary school. Epistles of Kızlar Hocası ve Hanımlar İlmihâli are discussed in terms of method, content and religious teaching.
Keywords: Din; Dinî Eğitim; Education; Eğitim; Kadınlar; Mehmed Zihni; Mehmed Zihni Religion; Religious Education; Women